AVAILABILITY ANALYSIS OF TWO SYSTEM WITH AND WITHOUT PREVENTIVE MAINTENANCE - Gupta, Praveen; Vinodiya, Pooja (International Journal of Computer Sciences and Engineering, 2025)
This paper deals with two systems have a single unit with two dissimilar components. The system remains operative even if a single component is in operative mode. The failure of one component creates change in life time parameter of other component. Both components can be replaced with a similar component. After replacement of each component, the system is as good as new. In second system Preventive maintenance (i.e. inspection, minor repair etc) is provide to system when system is in the state S0 where both components are normal mode